Paradoxical perception of object identity in visual motion. (July 2017) - Zharikova, Aleksandra; Gepshtein, Sergei; van Leeuwen, Cees
Abstract: In the course of perceptual organization, incomplete optical stimulation can evoke the experience of complete objects with distinct perceptual identities. According to a well-known principle of perceptual organization, stimulus parts separated by shorter spatial distances are more likely to appear as parts of the same perceptual identity. Whereas this principle of proximity has been confirmed in many studies of perceptual grouping in static displays, we show that it does not generalize to perception of object identity in dynamic displays, where the parts are separated by spatial and temporal distances. We use ambiguous displays which contain multiple moving parts and which can be perceived two ways: as two large objects that gradually change their size or as multiple smaller objects that rotate independent of one another. Grouping over long and short distances corresponds to the perception of the respectively large and small objects. We find that grouping over long distances is often preferred to grouping over short distances, against predictions of the proximity principle. Even though these effects are observed at high luminance contrast, we show that they are consistent with results obtained at the threshold of luminance contrast, in agreement with predictions of a theory of efficient motion measurement. This is evidence that the perception of object identity can be explained by a computational principle of neural economy rather than by the empirical principle of proximity.